2019
DOI: 10.33261/jaaru.2019.26.1.005
|View full text |Cite
|
Sign up to set email alerts
|

Single and Binary Adsorption of Cu(II) and Ni(II) Ions from Aqueous Solutions by Sunflower Seed Husk

Abstract: This research presents the possibility of using sunflower seed husk as an adsorbent for the removal of Cu+2 and Ni+2 ions from simulated aqueous solution. A series of experiments were carried out in a batch reactor to obtain equilibrium data for adsorption of single and binary metal solutions. Experiments parameters such as pH, sorbent dosage, contact time, agitation speed and initial metal ions concentration were studied to optimize the best conditions. The results showed that the best parameters were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Paulovics and Bokányi (7) examined chemically modified sunflower hulls and results confirmed that this material has higher ability to reduce Pb(II) and Cd(II) ions concentration from aqueous solution. Removal of copper ions was examined by some authors: Feizi and Jalali (8) and Abdulhussein and Al wared (9) have shown that sunflower husk has a very good binding affinity toward copper ions. However in our study obtained sorption capacity with the same sorbent and same metal was slightly higher (by 15 and 35%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Paulovics and Bokányi (7) examined chemically modified sunflower hulls and results confirmed that this material has higher ability to reduce Pb(II) and Cd(II) ions concentration from aqueous solution. Removal of copper ions was examined by some authors: Feizi and Jalali (8) and Abdulhussein and Al wared (9) have shown that sunflower husk has a very good binding affinity toward copper ions. However in our study obtained sorption capacity with the same sorbent and same metal was slightly higher (by 15 and 35%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/w14203298/s1, Figure S1: XRD patterns of pine sawdust, sunflower seed hulls, and corn residues mix; Table S1: Main results of literature studies about the adsorption of Ni(II), Zn(II) and Cd(II) on sawdust, sunflower and corn. References [44,52,[61][62][63][64][65][66][67] are cited in the "supplementary materials".…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Toxic metals can accumulate at any point in the food chain and have a detrimental effect on all living things since they are incapable of being broken down by living things. Therefore, it is crucial to create the methods capable of removing dangerous heavy metals out of contaminated wastewaters [12]. Harmful effects associated with heavy metals on people include vomiting, diarrhea, typhoid, cancer, and severe liver and kidney damage [13].…”
Section: Introductionmentioning
confidence: 99%